Screening evaluation of the ecotoxicity and genotoxicity of soils contaminated with organic and inorganic nanoparticles: the role of ageing - Pereira, R.
This study aimed to evaluate the toxicity and genotoxicity of soils, and corresponding elutriates, contaminated with aqueous suspensions of two organic (vesicles of sodium dodecyl sulphate/didodecyl dimethylammonium bromide and of monoolein and sodium oleate) and five inorganic nanoparticles (NPs) (TiO(2), TiSiO(4), CdSe/ZnS quantum dots, Fe/Co magnetic fluid and gold nanorods) to Vibrio fischeri and Salmonella typhimurium (TA98 and TA100 strains). Soil samples were tested 2 h and 30 days after contamination. Suspensions of NPs were characterized by Dynamic Light Scattering. Soils were highly toxic to V. fischeri, especially after 2 h. After 30 days toxicity was maintained only for soils spiked with suspensions of more stable NPs (zeta potential >30 mV or <-30 my). Elutriates were particularly toxic after 2 h, except for soil spiked with Fe/Co magnetic fluid, suggesting that ageing may have contributed for degrading the organic shell of these NPs, increasing the mobility of core elements and the toxicity of elutriates. TA98 was the most sensitive strain to the mutagenic potential of soil elutriates. Only elutriates from soils spiked with gold nanorods, quantum dots (QDs) and TiSiO(4) induced mutations in both strains of S. typhimurium, suggesting more diversified mechanisms of genotoxicity. (C) 2011 Elsevier B.V. All rights reserved.